2016
DOI: 10.7554/elife.10473
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic NF-κB and E2F interactions control the priority and timing of inflammatory signalling and cell proliferation

Abstract: Dynamic cellular systems reprogram gene expression to ensure appropriate cellular fate responses to specific extracellular cues. Here we demonstrate that the dynamics of Nuclear Factor kappa B (NF-κB) signalling and the cell cycle are prioritised differently depending on the timing of an inflammatory signal. Using iterative experimental and computational analyses, we show physical and functional interactions between NF-κB and the E2 Factor 1 (E2F-1) and E2 Factor 4 (E2F-4) cell cycle regulators. These interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 80 publications
1
51
1
1
Order By: Relevance
“…This mechanism might also involve maintenance of the cellular NF-B concentration independently of the cell size, as we previously observed (38). Alternative mechanisms might involve a specific gating of the inflammatory response through the cell cycle system, for example, through modulation of NF-B dynamics (55). Further studies will be required to understand precisely how the observed target gene expression (and protein secretion) correlates with heterogeneous NF-B dynamics in single cells (56) and how it is influenced by other factors, for example, potential augmentation of the TLR response through paracrine or autocrine signaling (20,21).…”
Section: Discussionmentioning
confidence: 66%
“…This mechanism might also involve maintenance of the cellular NF-B concentration independently of the cell size, as we previously observed (38). Alternative mechanisms might involve a specific gating of the inflammatory response through the cell cycle system, for example, through modulation of NF-B dynamics (55). Further studies will be required to understand precisely how the observed target gene expression (and protein secretion) correlates with heterogeneous NF-B dynamics in single cells (56) and how it is influenced by other factors, for example, potential augmentation of the TLR response through paracrine or autocrine signaling (20,21).…”
Section: Discussionmentioning
confidence: 66%
“…Experiments were performed on three cell models: human neuroblastoma SK-N-AS cells transfected with RelA-dsRedXP plasmid, SK-N-AS cells stably expressing an IkBα-eGFP BAC as described previously ( 29 , 30 ), and primary mouse adult fibroblasts (MAFs) cultured from ear punches from transgenic mice expressing an RelA-DsRed XP BAC ( SI Appendix ). SK-N-AS cells were cultured in Modified Eagles Medium supplemented with 1% nonessential amino acids (Sigma-Aldrich), and MAFs were cultured in Dulbecco Modified Eagles Medium.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade, cutting-edge microscopy approaches have demonstrated that this two-feedback structure can support oscillations of the nuclear NF-κB in response to cytokine stimulation, including Tumor Necrosis Factor α (TNFα) [ 11 , 12 ]. These analyses exemplify how complex environmental signals may be functionally encoded in the dynamical NF-κB system response [ 13 ], which is in part facilitated by crosstalk with other cellular signaling systems [ 14 , 15 ]. For example, the treatment dose regulated the number of responding cells in the population, exhibiting digital (binary) on-off activation [ 16 18 ], while the timing and amplitude of the NF-κB response controls target gene expression [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%